2015
DOI: 10.12693/aphyspola.127.99
|View full text |Cite
|
Sign up to set email alerts
|

Acoustically Active Antibubbles

Abstract: In this study, we analyse the behaviour of antibubbles when subjected to an ultrasonic pulse. Specically, we derive oscillating behaviour of acoustic antibubbles with a negligible outer shell, resulting in a RayleighPlesset equation of antibubble dynamics. Furthermore, we compare theoretical behaviour of antibubbles to behaviour of regular gas bubbles. We conclude that antibubbles and regular bubbles respond to an acoustic wave in a very similar manner if the antibubble's liquid core radius is less than half t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 10 publications
2
26
0
Order By: Relevance
“…Below this ratio, the harmonic component was too small to be detected. Examples of numerical simulations of the acoustic response from bubbles and antibubbles without an encapsulating shell have also been presented in [7], indicating a significant higher harmonic content of antibubbles compared to conventional bubbles.…”
Section: L Gmentioning
confidence: 99%
“…Below this ratio, the harmonic component was too small to be detected. Examples of numerical simulations of the acoustic response from bubbles and antibubbles without an encapsulating shell have also been presented in [7], indicating a significant higher harmonic content of antibubbles compared to conventional bubbles.…”
Section: L Gmentioning
confidence: 99%
“…Noticeably, it has recently been suggested that leaks from subsea hydrocarbon production facilities contain antibubbles with a specific acoustic signature [5]. Nowadays, benefiting from the development of microfluidics, several potential applications have arisen, such as using antibubbles as contrast agent for enhancing ultrasonic imaging [6,7] or loading the antibubble core with a ferrofluid to serve as a vehicle for magneto-controlled drug delivery [8].…”
Section: Introductionmentioning
confidence: 99%
“…Since antibubbles have spherical symmetry and might be expected to undergo breathing mode oscillations analogous to those described by the Rayleigh-Plesset equation, a first approximation to an antibubble acoustical model can be made using some minor modifications to this wellestablished model for normal bubbles. We note that Kotopoulis et al 34 derived a version of the Rayleigh-Plesset equation for antibubbles from first principles, but we will outline another model here, which includes some empirical components, for reasons that are discussed below.…”
Section: Modification Of the Rayleigh-plesset Equation For Antibubmentioning
confidence: 99%